2008
DOI: 10.1007/s11033-008-9412-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and expression pattern of AFPIV during embryogenesis in gibel carp(Carassiu auratus gibelio)

Abstract: As a new type of AFPs,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…AFPIV was first identified as an antifreeze protein in teleost blood plasma [14,15], and abundant expression was detected during carp embryogenesis [41] and in an Atlantic cod ovary EST library [23]. Prior research in cod, however, has found no antifreeze activity in eggs and larvae [69], and AFPIV function as an antifreeze protein is unclear, as it only renders low thermal hysteresis [22] and is structurally similar to apolipoproteins (lipid-binding proteins) from many fish species.…”
Section: Lipid Metabolismmentioning
confidence: 99%
“…AFPIV was first identified as an antifreeze protein in teleost blood plasma [14,15], and abundant expression was detected during carp embryogenesis [41] and in an Atlantic cod ovary EST library [23]. Prior research in cod, however, has found no antifreeze activity in eggs and larvae [69], and AFPIV function as an antifreeze protein is unclear, as it only renders low thermal hysteresis [22] and is structurally similar to apolipoproteins (lipid-binding proteins) from many fish species.…”
Section: Lipid Metabolismmentioning
confidence: 99%
“…Following our systematic studies on maternal factor screening and gene function identification 9-13 in polyploid gibel carp ( Carassius auratus gibelio , Cag ) with multiple modes of unisexual and sexual reproduction 14-19, we have also identified and characterized a type-IV antifreeze protein gene ( afp4 ) 20. Antifreeze proteins (AFPs) have been found in fungi, bacteria, plants and animals, and they can bind to ice crystals to inhibit growth and recrystallization of ice 21.…”
Section: Introductionmentioning
confidence: 99%
“…According to their molecular structures, four types of AFPs, type I-IV AFPs, have been characterized in teleost fishes 22. The type-IV antifreeze protein (AFP4) was firstly discovered from longhorn sculpin ( Myoxocephalus octodecimspinosis ) in 1997 23, and its homologues had been identified in other teleost fishes, ranging from polar to tropic region and from seawater to freshwater 20, 24, 25. As a new type of AFP, their molecular structures have been characterized by the conserved four-helix bundle 24-26, and the antifreeze activity has been demonstrated in several fishes 23-26.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, if longhorn sculpin AFP IV had been evolved only through the selective pressure of the cold Antarctic environment approximately 10-15 million years ago, then there would likely be a very slim chance of comparable AFP IV evolution in temperate, subtropical, and/or tropical fish such as P. olivaceus, which might have experienced very recent temporal glaciation approximately 2.5 to 3 million years ago. Instead, the abundant expression of AFP IVs in carp and zebra fish observed in oocytes and embryos strongly support its association with early development (Goetz et al 2006;Liu et al 2009;Brenton et al 2012). …”
Section: Discussionmentioning
confidence: 97%
“…Based on the initial characterization of two AFP IVs from longhorn and shorthorn sculpins, Gauthier et al (2008) speculated that AFP IV may not have been selected and evolved as a main antifreeze owing to the presence of the more efficient type I AFP. In addition, very recently, a Chinese group reported that two AFP IV genes, afp4a and afp4b, from the tropical fish gibel carp (Carassius auratus gibelio) and zebrafish (Danio rerio) are essential for epiboly progression and convergent movement during zebrafish embryo gastrulation (Liu et al 2009;Lee et al 2011;Xiao et al 2014). This evidence is consistent with previous findings that some apolipoproteins, which are homologues of AFP IV, play a significant role in embryonic morphogenesis and organogenesis in these fish (Xia et al 2008;Choudhury et al 2009;Zhang et al 2011;Wang et al 2013;Xiao et al 2014).…”
Section: Introductionmentioning
confidence: 99%